Public Perception on Transparency and Trust in Government Information Released During the COVID-19 Pandemic - Alila Pramiyanti; Ira Dwi Mayangsari; Reni Nuraeni; Yasinta Darin Firdaus (Asian Journal for Public Opinion Research)
A low level of transparency and trust in the release of government information during the COVID-19 pandemic could decrease the chance of success in handling the coronavirus outbreak. This worldwide pandemic has damaged not only human health but also created an economic and social crisis. Indonesia is no exception. Unfortunately, an analysis of a mixed-method survey of 500 participants found that public perception of transparency in the government’s release of COVID-19 information is still at a low level. This perceived low level of transparency generates minimum trust in the information. Only 8% of participants trust the government’s information regarding the virus. Even though the Indonesian government launched an official website, www.covid19.go.id, which is intended as a primary source of valid information about COVID-19 in Indonesia, most survey participants had never used the website. However, contrary to the low levels of perceived transparency and trust, most participants said that the messages from the government are clear and easy to understand. This contradiction resulted from skepticism toward the government. Therefore, this research presents a better understanding of how the level of transparency and trust is also related to the level of skepticism of the government.